Tablet Formula Optimization From Helminthostachys Zaylanica Extract Using A Simplex Lattice Design - Fitrya Fitrya; Najma Annuria Fithri; Budi Untari; Aprililianti (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2021)
Helminthostachys zeylanica extract has pharmacological activities such as antioxidant, antiinflamatory, and antihyerucemia. This extract is nontoxic substance from the acute and subchronic toxicity tests. This extract has a potency to be formulated into tablet dosage forms. This study aims to optimize a tablet formula from Helminthostachys zeylanica extract. Disintegrant and binder concentrations were independent variables, while physical properties and dissolution time of the tablets were dependent variables. The tablet was prepared by a wet granulation method. Formula was optimized by Simplex Lattice Design. Physicochemical propertiesof granule, physical properties and dissolution of tablet were then analyzed with One Way ANOVA (p = 0.05). Based on granule analysis, specification of physicochemical parameters, such as hausner’s ratio, compressibility index, flowability, repose angle, and water content, met standard British Pharmacopeia. In addition, the starch and PVA concentrations influenced thickness, weight variation, hardness, friability, disintegration time and dissolution of the tablets (p <0.05), except for friability (p> 0.05). Based on this study, the starch and PVA concentrations for the optimum tablet formula were 19.5% and 1.05%, respectively.